STUDY ON BAMBOO RHIZOBACTERIA TO RED ONION VARIETY GROWTH (Allium ascalonicum L.) - Yekti Maryani (Jurnal Agrivet, 2018)
The research was conducted in Gamol, Balecatur, Gamping, Sleman regency, Indonesia. The research aimed to study bamboo rhizobacteria to red onion three variety growth. The research was arranged in a Split Plot Design. The main factor was red onion variety, namely Bima, Biru and Thailand. The sub factor was bamboo rhizobacteria concentration, include 0%, 0.75% and 1.5%. The variables include hight of plant, number of leave, number of plant, fresh weight of plant, dry weight of plan. Data were analysed by analysis of variance of 5% significance level. The results that there wasn’t interaction between the red onion variety and bamboo rhizobacteria on all of variables. Rhizobacteria bamboo increase Sum Growth Rate and Tolerance Index. Thailand Variety of red onion put up the highest Sum Growth Rate.Key words: red onion, varietas, bamboo, rhizobacteria, growth